Statistical and computational methods in brain image analysis - Chung, Moo K. (Boca Raton : CRC Press, 2014)
c
1. Introduction to brain and medical images -- 2. Bernoulli models for binary images -- 3. General linear models -- 4. Gaussian kernel smoothing -- 5. Random fields theory -- 6. Anisotropic kernel smoothing -- 7. Multivariate general linear models -- 8. Cortical surface analysis -- 9. Heat kernel smoothing on surfaces -- 10. Cosine series representation of 3D curves -- 11. Weighted spherical harmonic representation -- 12. Multivariate surface shape analysis -- 13. Laplace-Beltrami Eigenfunctions for surface data -- 14. Persistent homology -- 15. Sparse networks -- 16. Sparse shape models -- 17. Modeling structural brain networks -- 18. Mixed effects models.
Includes bibliographical references (p. 363-396) and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Brain -- Imaging; Brain -- Imaging -- Statistical methods; Brain mapping -- Statistical methods; Electronic books